Региональное сотрудничество в области безопасности полетов: международно-правовые вопросы - A. A. Batalov (Московский журнал международного права, 2022)
INTRODUCTION. Based on the analysis of documents and practice of numerous regional international organizations and other present-day forms of regional interstate cooperation in the area of aviation safety and aircraft accident investigation the article examines different international legal issues arising out of such cooperation, including, in particular, the legal nature, powers and membership of these regional international organizations.MATERIALS AND METHODS. The present research has been conducted on the basis of international air law treaties, constituent instruments and decisions of various regional international organizations, the ICAO documents, as well as the works of Russian and foreign international law experts. The methodology of the research is based upon general scientific and special methods, including dialectical method, methods of analysis and synthesis, deduction and induction, comparative legal method.RESEARCH RESULTS. On the basis of his research the author has been able to identify and classify all presentday forms of regional interstate cooperation in the area of aviation safety and aircraft accident investigation, define the legal nature of such forms, examine theoretical and practical international legal issues relating thereto as well as propose recommendations aimed at resolving these issues.DISCUSSION AND CONCLUSIONS. The advantages and the important role of regional cooperation of States in the area of aviation safety oversight and aircraft accident investigation are underlined in the article. However, despite the importance of such cooperation for enhancement of aviation safety, currently its development depends upon the successful resolution of the following problems: – improvement of international legal framework (e.g., international treaties, decisions of international organizations etc.), which governs establishment and functioning of aviation safety oversight and aircraft accident investigation regional international organizations and bodies, in particular, with the aim to expand their powers to perform more complex and important functions in the area of aviation safety oversight and accident investigation for their Member States (e.g., certification of aeronautical products and other civil aviation facilities, conducting full accident investigation etc.); – ensuring more sustainable funding for aviation safety oversight and aircraft accident investigation regional international organizations and bodies; – training of bigger number of aviation professionals performing inspectorial functions in the area of aviation safety oversight as well as aircraft accident and incident investigation functions; – limitation of cases of simultaneous membership of the same States in several aviation safety oversight and aircraft accident investigation regional international organizations. Resolving the problems mentioned above, in particular, on the basis of recommendations proposed in this article, will allow to increase the efficiency and attractiveness of different forms of regional cooperation in the area of aviation safety oversight and aircraft accident investigation for bigger number of States, as well as help to improve regional cooperation of the Russian Federation within the framework of the Eurasian Economic Union and the Commonwealth of Independent States in this area.